Board of director’s gender diversity and its impact on earnings management: an empirical analysis for select European firms - Saona, Paolo; Muro, Laura; San Martín, Pablo; Baier-Fuentes, Hugo (Technological and Economic Development of Economy, 2019)
From a corporate governance point of view, this paper addresses the question about how board gender diversity influences managerial opportunistic behavior for solving agency conflicts from a sample of European countries. Specifically, we analyzed indexed non-financial companies from Denmark, Finland, France, Germany, Italy, Norway, Portugal, Spain, Sweden, and United Kingdom for the period 2006–2016. Several panel data techniques are used in the empirical analysis to deal with the endogeneity and heterogeneity problems. To the best of our knowledge our research is novel in the literature by providing a multi-country approach in board gender diversity, as well as considering contextual country variables and the role of the regulatory system as determinants of earnings management. Our results confirm the benefits of having a balanced board in terms of gender diversity. An equilibrated board tends to mitigate earnings management practices, reinforcing the value of the laws passed in recent decades in Europe. Our analysis reveals that the regulatory framework regarding board gender diversity established by each country has a determinant role in reaching equality in decision-making positions, as a founding value of the European Union. We provide several policy recommendations from our main findings.